Unveiling miRNA30b’s Role in Suppressing ADAM12 to Combat Triple-Negative Breast Cancer - Qing-hua Yin; Jian-bing Hu; Qiang Zhou; Jie Weng; Er-dong Shen; Fang Wen; Song-lian Liu; Lei-lan Yin; Ya-jun Tong; Ling Long; Ke-wei Tang; Si-te Bai; et al. (The Breast Journal)
Conclusions: miRNA30b could promote proliferation, migration, and invasion of TNBC cell lines MDA-MB-231. The effect of miRNA30b on triple-negative breast cancer would be achieved partly at least through inhibiting the expression of ADAM12.